Model Pendeteksi Api dalam Ruangan Berbasis SMS Menggunakan Logika Fuzzy - Ardiansyah, Deden; Anjani, Anjyaz (Universitas Trilogi, 2019)
Automation system in its function to helps and makes human life easier has experienced a significant growth in recent years, for example in security field. Low security level such as no fire detection system is one of the factors which is supporting the possibilities of fire accidents to happen. This system detects the possibilities fire using fuzzy logic. This system uses microcontroller Arduino Uno as control unit, flame sensor to check infrared ray from the fire, DHT11 temperature sensor to monitor the temperature in the room, and GSM shield to send SMS. Sensors will detect fire in the room and send the collected information to be processed by Arduino Uno by implementing fuzzy logic. SMS-Based Indoor Fire Detection System Models Using Fuzzy Logic has many benefits in the development of room safety systems from fire hazards. The design of this system is simple but can be widely applied to further research development.